(untitled) (Palíndromo, 2013)
The concept related to the gift seems to have been absent from discussions artistic after the avant-garde of the twentieth century, however Jacques Derrida rehabilitates the notion of gift, through the conception proposed by Marcel Mauss and Charles Baudelaire. This essay discusses the different theoretical perspectives on the concept associated to the gift of artistic creation. The artist would be preceded by the gift which would have instilled innate artistic characteristics or it would have been forged through the tireless dedication and commitment to the job? Through a diachronic perspective, we try to understand the oscillation and concurrence between both discursive approaches.